The Role of Angiogenesis Factor in Bladder Tumors - Jawed , Sanaa (University of Thi-Qar Journal of Science, 2019)
The study designed to detect Ang-1 expression as angiogenesis factor in bladder tumor tissues, and to clarify the relationship between Ang-1 and clinicopathological grade of bladder cancer. In this study, the expression of Ang-1 in tumor cells was investigated in (30) patients with transitional cell carcinoma of bladder (TCC) and (20 ) patients with inflammatory lesions of the bladder (BIL) as acontrol group from the histopathology laboratories of Al-Hussain Teaching Hospital and private laboratories in Thi-Qar Province,Iraq . The tissue sections were analyzed immunohistochemically (IHC) to detection of Ang-1. The results showed a high positive immunohistochemical Ang-1 expression of TCC tissues than in BT tissues (76.7 % versus 40%; p≤ 0.01). Furthermore, the significantly highest level of Ang-1 positive cells was detected in the groups with the highest clinical grade (p≤ 0.05). Ang-1 antigen expression could be indicator of aggressive behavior of bladder cancer